Analisis Keanekaragaman Hayati di Kawasan Konservasi Gua Pawon Kecamatan Cipatat Bandung Barat Sebagai Informasi Pendidikan - Hamzah, A. Hadian Pratama; Hadiat, MH. Anang; Nurhasanah, Nurhasanah (Jurnal Simki Pedagogia, 2023)
The Pawon Cave conservation area is a karst area that has a potential mining threat that can damage cultural heritage objects, catchments and springs, karst landscapes, flora and fauna. This study aims to examine the sustainability of the conservation of the Pawon Cave area from the aspect of biodiversity. The method used is a mixture of qualitative and quantitative. The results showed that from the aspect of biodiversity in the Pawon Cave conservation area, there are several springs that are quite good in the rainy season and dry season, but there are still obstacles in the distribution of utilization for residents around the beneficiary area. Processing and minimization of soil erosion is well managed, including the terracing system. Plants and animals that live in the area are preserved in the absence of logging and hunting. As for several types of plants in the suspected area, there are teak (Tectona grandis), mahogany (Swietenia mahagoni), manglid (Manglieta glauca), acacia (Acacia auriculiformis) and several types of bamboo. The types of animal dominance found in the area are long-tailed monkeys and mouse deer as well as several reptiles Factors that influence the sustainability of the conservation of the Pawon Cave area are policy support from the government and having adequate human resources to manage the area. The implementation of the policy has shown that it is appropriate to support conservation efforts such as prevention of mining, preservation of springs, protection of plants and animals in the area.